Experimental Comparison of FPGA-Implemented Model Predictive Voltage Control to Cascaded Proportional Resonant Control for a Three-Phase Four-Wire Three-Level Grid-Forming Inverter of 250 kVA - Lange, Jarren; Schmies, Dominik; Stille, Karl Stephan Christian; Böcker, Joachim; Wallscheid, Oliver (EPE'22 ECCE Europe)

Emulation of Microgrids for Research and Validation of Control and Operation Strategies - Stille, Karl Stephan Christian; Weber, Daniel; Lange, Jarren; Vogt, Thorsten; Wallscheid, Oliver; Böcker, Joachim (2020 International Symposium on Power Electronics, Electrical Drives, Automation and Motion (SPEEDAM))

Energy Management for a Nano-CHP Unit and an Electrical Storage System in a Residential Application - Weber, Daniel; Stille, Karl Stephan Christian; Wallscheid, Oliver; Böcker, Joachim (2018 International Symposium on Power Electronics, Electrical Drives, Automation and Motion (SPEEDAM))

Energiemanagement von Haushaltsgroßgeräten - Stille, Karl Stephan Christian

Local demand response and load planning system for intelligent domestic appliances - Stille, Karl Stephan Christian; Böcker, Joachim (2015 International Conference on Renewable Energy Research and Applications (ICRERA))

Integration of home photovoltaic generation into electricity tariff for load optimization - Stille, Karl Stephan Christian; Böcker, Joachim; Fröhleke, Norbert; Bettentrup, Ralf; Kaiser, Ingo (2016 4th International Istanbul Smart Grid Congress and Fair (ICSG))

Local grid load coordination for load-shiftable domestic appliances in a variable-tariff environment - Stille, Karl Stephan Christian; Böcker, Joachim; Fröhleke, Norbert; Bettentrup, Ralf; Kaiser, Ingo (2016 18th European Conference on Power Electronics and Applications (EPE'16 ECCE Europe))

Supervisional load optimization for households with intelligent domestic appliances - Stille, Karl Stephan Christian; Böcker, Joachim; Fröhleke, Norbert; Bettentrup, Ralf; Kaiser, Ingo (2016 10th International Conference on Compatibility, Power Electronics and Power Engineering (CPE-POWERENG))

Concept for a hierarchical load control for domestic appliances in smart grids - Stille, Karl Stephan Christian; Böcker, Joachim; Bettentrup, Ralf; Kaiser, Ingo (2014 International Conference on Advances in Green Energy (ICAGE))

Hierarchisches Optimierungskonzept für die Laststeuerung von Haushaltsgeräten - Stille, Karl Stephan Christian; Böcker, Joachim; Bettentrup, Ralf; Kaiser, Ingo (ETG-Fachtagung "Von Smart Grids zu Smart Markets")
Haushaltsgeräte aus der Klasse der "Weißen Ware" tragen mit etwa einem Drittel ($34,2%$ \citeBDEW2013) zum privaten Energieverbrauch bei. Diese Veröffentlichung präsentiert eine Struktur und die dafür notwendige optimale Betriebsstrategie für Weiße Ware in einer Umgebung mit Strompreisen, die wegen der Volatilität der Regenerativen Energien stark fluktuieren. Das vorgeschlagene Konzept nutzt dafür ein dezentrales Energiemanagementsystem, das über drei Hierarchieebenen verteilt ist: die Geräteebene, die Haushaltsebene und die Ortsnetzebene. Auf der Geräteebene nutzt dieses Konzept zusätzlich Betriebsflexibilitäten der Haushaltsgeräte aus.
Keywords: Energy management; hybrid energy storage system; self-optimization; multi-objective optimization; adaptive systems; pareto set; SFB614-D1; SFB614-D2; LEA-Publikation; Eigene